EFFECT OF YOGA TRAINING ON SUPEROXIDE DISMUTASE IN ADULT - Yasa, Devi Paramita; Wahyuni, Nila (Sport and Fitness Journal; Vol 12 No 1 (2024): Volume 12, No. 1, January 2024, 2024)
Due to its capacity to enhance both physical and emotional well-being as well as to treat a number of medical illnesses like diabetes, cardiovascular disease, and chronic pain, yoga has become increasingly popular on a global scale. Yoga's ability to increase the body's antioxidant levels, especially those of superoxide dismutase (SOD), which may have anti-aging benefits, is one potential benefit. Although the precise mechanisms are still unclear, regular yoga practice has been found to raise SOD levels. Possible processes include hormesis-induced antioxidant defense mechanism stimulation and deep breathing-induced relaxation promotion and enhanced oxygenation. This review of the literature identifies gaps and restrictions in the research while providing an overview of the current studies on the impact of yoga on antioxidant levels. The ideal sort and length of yoga practice for maximum antioxidant benefits are still being determined, as are the mechanisms of action. Overall, practicing yoga may have the ability to increase antioxidant status and enhance general health and wellbeing. Keywords: yoga training; antioxidant